Enhancement of heat transfer coefficient in an automobile radiator by using nanocoolant - Mohd. Faizal Ali Akhbar (2015)
Enhancement of heat transfer phenomenon is gaining research importance in applications of various fields of engineering,from microelectronics to highly powered lasers.It is acknowledged that among three modes of heat transfer (conduction,convection and radiation);most of the heat transfer takes place by conduction and convection in many situations.However,the conventional approaches like extended surface,application of vibration to the heat transfer surfaces,usage of microchannels and additional fluid pumping power to the system were thought to have reached their limits.Hence,various attempts to increase thermal conductivity of the fluid itself have been made..The practical demonstration of this theory was initiated in the year 1995 by U.S Choi who came out with the term “Nanofluid”. Every system generating heat needs cooling arrangement in order to improve performance and for economical maintenance of the system.The initial effort of the present research study is to enhance the heat transfer phenomenon in a vehicle radiator by the application of nanofluids for higher thermal conductivity.In the recent years,few researchers worked on similar applications using nano particles such as Al2O3,CuO,SiO2,TiO2 and MWCNT’s and water or water with Ethylene Glycol as a coolant base fluids.However, all the investigations were limited to application of the nano coolants in experimental equipment.This paves the method for the present investigation in improvement of the heat transfer phenomenon by different factors affecting thermal conductivity in an automobile radiator. The effect of nanofluid heat transfer enhancement in water and coolant based systems with different nano particles and concentrations are investigated from an engineering system perspective. One such system considered is a “KELISA (1000cc) – CAR RADIATOR” cooling circuit using different nanofluids to replace the conventional engine coolant.Results include quantifications of increase in engine heat rejection for the coolant circuit by the use of nanofluids instead of the conventional coolant.